2017
DOI: 10.1111/nph.14895
|View full text |Cite
|
Sign up to set email alerts
|

Host preference and network properties in biotrophic plant–fungal associations

Abstract: Analytical methods can offer insights into the structure of biological networks, but mechanisms that determine the structure of these networks remain unclear. We conducted a synthesis based on 111 previously published datasets to assess a range of ecological and evolutionary mechanisms that may influence the plant-associated fungal interaction networks. We calculated the relative host effect on fungal community composition and compared nestedness and modularity among different mycorrhizal types and endophytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
127
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 78 publications
10
127
4
Order By: Relevance
“…Despite finding evidence for AM fungal specificity to host plant species, we did not find evidence for a phylogenetic signal of host plants on AM fungal community structure (Figure d). This finding is consistent with a synthesis study by Põlme et al () using previously published datasets. In a meta‐analysis, Veresoglou and Rillig () explored phylogenetic host specificity in AM fungal communities to reach a counter‐intuitive conclusion that closely related co‐occurring plants tend to have dissimilar AM fungal communities.…”
Section: Discussionsupporting
confidence: 93%
“…Despite finding evidence for AM fungal specificity to host plant species, we did not find evidence for a phylogenetic signal of host plants on AM fungal community structure (Figure d). This finding is consistent with a synthesis study by Põlme et al () using previously published datasets. In a meta‐analysis, Veresoglou and Rillig () explored phylogenetic host specificity in AM fungal communities to reach a counter‐intuitive conclusion that closely related co‐occurring plants tend to have dissimilar AM fungal communities.…”
Section: Discussionsupporting
confidence: 93%
“…The network of interacting plants and AM fungi in a dry calcareous grassland exhibited a significantly higher level of nestedness than would be expected from null models. Nested structure is typical of aboveground mutualistic interaction networks (Bascompte, Jordano, Melián, & Olesen, ); Põlme et al () also recorded a varying degree of nestedness both in endophytic and in belowground mycorrhizal and plant–fungal networks. Other studies, however, have not found nestedness in belowground plant–fungal interactions: in ectomycorrhizal (Bahram, Harend, & Tedersoo, ), ericoid mycorrhizal (Toju, Tanabe, & Ishii, ) or belowground plant–fungal networks in general (Toju, Guimarães, Olesen, & Thompson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons among mutualistic plant–fungal networks of different mycorrhizal type have indeed demonstrated common properties, such as relationships between network structure and climatic variables (Põlme et al, ). However, they have also indicated that descriptions of interaction network structure are critically sensitive to the number of locally sampled species (Põlme et al, ). In this study, we explored the interaction network formed by vascular plant species and root symbiotic AM fungi at a ca 1,000 m 2 dry calcareous grassland site.…”
Section: Discussionmentioning
confidence: 99%
“…However, these factors have less impact on root‐associated than on soil‐localized mycorrhizal fungi (Goldmann et al., ). In managed forests, silvicultural measures, especially the selection of tree species, influence mycorrhizal associations because of fungal host preferences (Lang, Seven, & Polle, ; Pena et al., ) and also because tree species‐specific traits influence habitat properties (Bahnmann et al., ; Põlme et al., ; Urbanová, Šnajdr, & Baldrian, ). However, at larger biogeographic scales of temperate forest ecosystems, the consequences of forest management on the taxonomic and trophic structure of RAMs are unknown.…”
Section: Introductionmentioning
confidence: 99%